Kualitas Hidup Pasien Diabetes Melitus Tipe 2 Di Puskesmas Se Kota Kupang - Margaretha Teli (JURNAL INFO KESEHATAN, 2017)
Diabetes Mellitus is well known as a chronic disease which can lead to a decrease in quality of life in all domains. The study aims to explore the diabetic type 2 patient’s quality of life and find out the factors affecting in type 2 diabetic mellitus patients. The cross-sectional study design is used that included 65 patient with type 2 diabetes mellitus, in 11 public health centers of Kupang City. Data were collected by using Short Form Survey (SF-36) that assessed 8-scale health profile. Independent sample t-test is used to analyze the correlation between the factors affecting and the quality of life. the study showed that the QoL of DM patients decreased in all 8- health profile including physical functioning, social functioning, mental health, general health, pain, change in the role due to physical problems and emotional problems. The Study also showed there was a relationship between gender, duration of suffering from Diabetes mellitus, and complications to the quality of life. Male perceived a better quality of life than female.